Polymorphism Ratio Sequencing: A New Approach for Single Nucleotide Polymorphism Discovery and Genotyping - Blazej, Robert G.; Paegel, Brian M.; Mathies, Richard A. (Genome Research, 2003)
Polymorphism ratio sequencing (PRS) combines the advantages of high-throughput DNA sequencing with new labeling and pooling schemes to produce a powerful assay for sensitive single nucleotide polymorphism (SNP) discovery, rapid genotyping, and accurate, multiplexed allele frequency determination. In the PRS method, dideoxy-terminator extension ladders generated from a sample and reference template are labeled with different energy-transfer fluorescent dyes and coinjected into a separation capillary for comparison of relative signal intensities. We demonstrate the PRS method by screening two human mitochondrial genomes for sequence variations using a microfabricated capillary array electrophoresis device. A titration of multiplexed DNA samples places the limit of minor allele frequency detection at 5%. PRS is a sensitive and robust polymorphism detection method for the analysis of individual or multiplexed samples that is compatible with any four-color fluorescence DNA sequencer.